PROCESS OF PRODUCING ELECTRIC POWER FROM PLANTS - Dr. Aparna Jha , Dr. Alka Shukla (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
The power created from coal, gaseous petrol also, other petroleum product are non-sustainable. The discharge during the development of power utilizing these sources is hurtful to the climate. After some timeframe, these sources will become terminated. Thus, we want a more reasonable type of energy. In this paper we present a technique for gathering electrical energy from living plants. Plants store substance energy in their foundations as synthetic sugar bonds. At the point when cathodes are set in the roots, the particles move towards the terminals and this progression of particles produce power. The cathodes utilized in this research are copper and iron. The general reason for this research is to deliver power utilizing more manageable sources. The plant utilized for this research is teak.